2015
DOI: 10.1007/s40843-015-0070-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of intermetallic compounds of Cu/Al multilayer foils during cold rolling

Abstract: Sci China Mater 2015, 58: 574-583 ening may prevent severe plastic deformation. Therefore, understanding whether chemical reactions can occur and new phases can be formed during producing multi-layered composites by severe plastic deformation is important. However, these behaviors are not well understood. Accordingly, the occurrence of chemical reactions in heavily strained dissimilar metals at room temperature must be demonstrated.We want to determine the behavior of a laminated-metal composite when pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The synthesis of IM phases typically requires high temperature; therefore, the design of IM nanoparticle (NP) catalysis with high surface areas is proven to be challenging. During the past few years the development of low-temperature solution-chemistry strategies for synthesizing IMNPs includes various methods such as coreduction, colloidal, hydrothermal synthesis, etc. ,, The formation of IMCs depends upon the mixing mode of each constituent element, its chemical composition, redox potential, structural properties, and the morphology of the particles . IMCs have potential in the field of catalysis, as they provide an ideal opportunity to study the correlation between the atomic ordering and the catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of IM phases typically requires high temperature; therefore, the design of IM nanoparticle (NP) catalysis with high surface areas is proven to be challenging. During the past few years the development of low-temperature solution-chemistry strategies for synthesizing IMNPs includes various methods such as coreduction, colloidal, hydrothermal synthesis, etc. ,, The formation of IMCs depends upon the mixing mode of each constituent element, its chemical composition, redox potential, structural properties, and the morphology of the particles . IMCs have potential in the field of catalysis, as they provide an ideal opportunity to study the correlation between the atomic ordering and the catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al reported the formation of interfacial Al–Cu ICs via cold rolling [ 18 ]. According to their report, the dislocations accumulated near the interfaces owing to compaction pressure weakened the inter-atomic bonding forces between the individual Al (or Cu), leading to their higher diffusivity [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, ICs are formed via thermal diffusion when heat is applied. A recent study revealed that ICs were partially formed at the interface between Al and Cu foils owing to the non-uniform accumulation degree of dislocations achieved via cold rolling (uniaxial high pressing) [ 18 , 19 ]. As the partial formation of ICs can enable direct contact between the metals at the interface, this approach was considered suitable for preventing the deterioration in thermal conductivity with an increase in the Al/Cu interface area.…”
Section: Introductionmentioning
confidence: 99%